Human surrogate models of central sensitization: A critical review and practical guide. (8th May 2021) - Quesada, Charles; Kostenko, Anna; Ho, Idy; Leone, Caterina; Nochi, Zahra; Stouffs, Alexandre; Wittayer, Matthias; Caspani, Ombretta; Brix Finnerup, Nanna; Mouraux, André; Pickering, Gisèle; Tracey, Irene; et al.
Abstract: Background: As in other fields of medicine, development of new medications for management of neuropathic pain has been difficult since preclinical rodent models do not necessarily translate to the clinics. Aside from ongoing pain with burning or shock‐like qualities, neuropathic pain is often characterized by pain hypersensitivity (hyperalgesia and allodynia), most often towards mechanical stimuli, reflecting sensitization of neural transmission. Data treatment: We therefore performed a systematic literature review (PubMed‐Medline, Cochrane, WoS, ClinicalTrials) and semi‐quantitative meta‐analysis of human pain models that aim to induce central sensitization, and generate hyperalgesia surrounding a real or simulated injury. Results: From an initial set of 1569 reports, we identified and analysed 269 studies using more than a dozen human models of sensitization. Five of these models (intradermal or topical capsaicin, low‐ or high‐frequency electrical stimulation, thermode‐induced heat‐injury) were found to reliably induce secondary hyperalgesia to pinprick and have been implemented in multiple laboratories. The ability of these models to induce dynamic mechanical allodynia was however substantially lower. The proportion of subjects who developed hypersensitivity was rarely provided, giving rise to significant reporting bias. In four of these models pharmacological profiles allowed to verify similarity to some clinical conditions, and therefore may inform basic research for new drug development. Conclusions: While there is no single "optimal" model of central sensitization, the range of validated and easy‐to‐use procedures in humans should be able to inform preclinical researchers on helpful potential biomarkers, thereby narrowing the translation gap between basic and clinical data. Significance: Being able to mimic aspects of pathological pain directly in humans has a huge potential to understand pathophysiology and provide animal research with translatable biomarkers for drug development. One group of human surrogate models has proven to have excellent predictive validity: they respond to clinically active medications and do not respond to clinically inactive medications, including some that worked in animals but failed in the clinics. They should therefore inform basic research for new drug development.